The ex-ante impact of conflict over infrastructure settings on residential property values: The case of Paris's suburban zones. (October 2015) - Torre, Andre; Pham, Vu Hai; Simon, Arnaud
The presence of nearby public facilities has an impact on real-estate values; for this reason, the market may reasonably anticipate that public infrastructure projects will affect house prices. But undesirable and semi-desirable facility location choices may be contested by nearby residents, as they are a source of negative externalities or expectations. In Paris's suburban zones, opposition to these infrastructures is frequent, and the official announcement of a project does not automatically mean it will be implemented. Through three case studies, we explore the way in which the expectation mechanism is affected by legal conflicts driven by nearby residents. We suppose that expectations depend on the probability that a given project will be realised. The variation is captured by a hedonic model. As conflicts amplify or reduce the certainty of the new facility's arrival, market perceptions of the infrastructure vary.